ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS V SEKOLAH DASAR PADA MATERI PECAHAN MELALUI BANTUAN TUTOR SEBAYA - Miyen Rara Sapitri; Irfan Supriatna; Yuli Amaliyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyse the mathematical comprehension ability of grade V elementary school students on fraction material through the help of peer tutors. The research method used was descriptive qualitative with observation, interview, and document analysis techniques. The research subjects were grade V students who had difficulty in understanding fractions, while peer tutors were selected based on academic and communication skills. The results showed that peer tutor assistance was effective in providing students' mathematical understanding, especially in re-explaining concepts, classifying objects based on concept requirements, implementing concepts algorithmically, and presenting examples. Interaction with peer tutors created a more comfortable learning atmosphere and encouraged students to be more active in asking questions and discussing. Thus, peer tutor assistance proved to be effective in providing students' mathematical understanding on fraction materials. This research can be a reference in developing more innovative and interactive learning strategies in primary schools. Keywords: Mathematical Understanding, Fractions, Peer Tutor